Real-world health services utilisation and outcomes after BRCA1 and BRCA2 testing in Ontario, Canada: the What Comes Next Cohort Study protocol. Issue 9 (4th September 2018) - Dossa, Fahima; Cusimano, Maria C; Sutradhar, Rinku; Metcalfe, Kelly; Little, Tari; Lerner-Ellis, Jordan; Eisen, Andrea; Meschino, Wendy S; Baxter, Nancy N
Abstract : Introduction: Women who have pathogenic mutations in the BRCA1 and BRCA2 genes are at greatly increased risks for breast and ovarian cancers. Although risk-reduction strategies can be undertaken by these women, knowledge regarding the uptake of these strategies is limited. Additionally, the healthcare behaviours of women who receive inconclusive test results are not known. This study protocol describes the creation of a retrospective cohort of women who have undergone genetic testing for BRCA1 and BRCA2, linking genetic test results with administrative data to quantify the uptake of risk-reduction strategies and to assess long-term cancer and non-cancer outcomes after genetic testing. Methods and analysis: Approximately two-thirds of BRCA1 and BRCA2 testing in Ontario, Canada is performed at North York General Hospital (NYGH) and Mount Sinai Hospital (MSH), Toronto. We will use registries at these sites to assemble a cohort of approximately 17 000 adult women who underwent BRCA1 and BRCA2 testing from January 2007 to April 2016. Trained chart abstractors will obtain detailed information for all women tested over this period, including demographics, personal and family cancer histories and genetic test results. We will link these data to provincial administrative databases, enabling assessment of healthcare utilisation and long-term outcomes after testing. Study outcomes will include the uptake of breast cancer screening and prophylactic breast and ovarian surgery, cancer incidence and mortality and incidence of non-cancer health outcomes, including cardiovascular, osteoporotic and neurodegenerative disease. Ethics and dissemination: This study has been approved by the Research Ethics Boards at NYGH (no 16-0035), MSH (no 13-0124) and Sunnybrook Health Sciences Centre (no 275-2016). We plan to disseminate research findings through peer-reviewed publications and presentations at national and international meetings.